Do Tourism Receipts Contribute to the Sustainability of Current Account Deficits: a Case Study of Barbados. (24th July 2012) - Lorde, Troy; Lowe, Shane; Francis, Brian
ABSTRACT: Given Barbados' recent history of persistent current account deficits and reliance on tourism as a major source of foreign exchange and driver of the economy, this paper investigated the contribution of tourism receipts to the sustainability of Barbados' current account deficits. Utilizing an inter‐temporal budget approach, it was found that Barbados' current account deficits were weakly sustainable as a result of tourism's contribution, underscoring the island's dependence on the industry. Copyright © 2012 John Wiley & Sons, Ltd.